Development of Teaching Materials for Writing Short Stories Based on Local Wisdom of Riau "Batimang" Class XI High School Students - Solina, Irma; Elmustian, Elmustian; Sinaga, Mangatur (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Writing skills are productive skills and the highest skill in acquiring language because writing skills are acquired after listening, speaking and reading skills. Writing is an activity to train students' thinking skills to be more creative, productive, and expressive. This research aims to determine the feasibility of teaching materials for writing short stories based on Batimang local wisdom for class XI SMA students and to find out the results of writing short stories based on Batimang local wisdom for class This development research uses qualitative data analysis techniques and quantitative data analysis techniques. Qualitative data analysis is used to analyze data obtained during interviews and written notes in the form of suggestions, input and comments obtained in questionnaires during the feasibility test. Researchers identified the need for teaching materials for writing short stories for class XI high school students in Kampar Regency. The development of teaching materials is carried out based on aspects of the needs of students and teachers. Teaching materials that have been validated by experts in the fields of appropriateness of material and language, and media experts that have been revised are then tested in the classroom. Next, based on the responses of students and teachers, they are analyzed and conclusions are drawn. Teaching materials that have been validated by experts in the fields of appropriateness of material and language, and media experts that have been revised are then tested in the classroom. Next, based on the responses of students and teachers, they are analyzed and conclusions are drawn. Teaching materials for writing short stories based on local Riau wisdom "Batimang" can improve student learning outcomes. This can be seen from the field trial data with an average score of 58.67 in the pretest and 76.84 in the posttest. Student learning outcomes for short story writing material increased and achieved good category scores.